The Administrative and Educational Problems Facing Integrating People with Special Needs in Basic Government Schools in Tulkarm Governorate from the Teachers and Principals Perspective - Al-debee, Nael Mostafa; AL-Sharif, Mirvat Mousa (Journal of Educational and Psychological Sciences, 2020)
This study aimed to know the administrative and educational problems facing integrating people with special needs in basic government schools in Tulkarm Governorate from the viewpoint of teachers and managers, and to know the impact of the study variables (gender, educational qualification, years of experience) on administrative and educational problems facing integration of people with special needs In the basic public schools in Tulkarm Governorate from the point of view of teachers and administrators, and to this end the descriptive approach has been used And designing a questionnaire consisting of (20) paragraphs, distributed on a random stratified sample of (60) teachers and administrators in the basic government schools in Tulkarm Governorate: The study reached the following results: that the total degree of administrative and educational problems facing the integration of people with special needs in Basic public schools in Tulkarm Governorate have an average of (3.86 out of 5), and at the level of fields; the field of administrative problems got (3.87) and the field of educational problems got an average of (3.85) and all of them are verbal (large), and that there are no statistically significant differences for the problems Administrative and educational facing the integration of people with disabilities The special needs in the basic government schools in Tulkarm Governorate from the viewpoint of teachers and administrators are attributed to the study variables (gender, educational qualification, years of experience)Based on the results, the study recommended the need for special places to play for people with special needs, and to find treatment programs in the event of problems for those with special needs.
Keywords: Administrative and educational problems; special needs; government schools; Tulkarm Governorate